Impact of workplace deviance dimensions on job satisfaction among academics of universities in oman via top management support: The mediating role - Albusaidi M.J.K.; Islam M.K.; Jaaffar A.H.; Ateeq A. (Springer Science and Business Media Deutschland GmbH, 2025)
Purpose. The current study aims to investigate the impact of the workplace deviance factors (training and development, communication, and motivation) on job satisfaction via top management support in the higher education sector in Oman. Design/Methodology/Approach?A quantitative research method was adopted for selecting and analysing the data of the study. Besides, a questionnaire was used to collect the data from the sample of the study (i.e., 355 academic staff) who work at private and public universities in the Sultanate of Oman, of whom 355 participants were academics, representing 81% of the sample. The smart-PLS technique was used to conduct the statistical analysis of the collected data. Findings?The findings of this study revealed that the lack of training, communication, and motivation negatively impacts job satisfaction by academic staff. Furthermore, top management support positively influenced job satisfaction. Moreover, the results of this study showed that top management support significantly mediates the relationship between workplace dimensions of training and development, communication and motivation, and job satisfaction. Researchimplications?The study is also expected to be significant to academics, employees, students, and researchers attempting to shed light on workplace deviance and its impact on their job satisfaction through top management as a mediating effect, especially those working in the higher education sector in Sultanate of Oman and similar context. Originality/value?This research contributes by examining the workplace deviance role in bringing about job satisfaction in education, focusing on its role in a professional occupation and in developing education, society, and economy that is stable in the Sultanate of Oman. ? The Author(s).